Творчість Т. Шевченка в рецепції М. Петрова та О. Огоновського: до проблеми становлення шевченкознавства - Головій, Оксана; Goloviy, Oksana (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті встановлено, що перші наукові роботи з історії української літератури – написані російською мо¬вою «Нариси з історії української літератури ХІХ століття» М. Петрова та українськомовна «Історія літератури руської» О. Огоновського – вузлові щодо окреслення суспільно-політичної, культурної, мовної та літературо¬знавчої ситуації в Україні 1880–1890-х рр. М. Петров представляє «компромісну»/«еклектичну» позицію: він наводить докази панславістської світоглядної орієнтації Т. Шевченка з домінуванням симпатій до Росії та обґрунтовує думку про інтенсивний вплив імперського письменства на Кобзаря та всю українську літературу. Натомість О. Огоновський доводить самостійність і органічність української культури. Згідно з його концепцією творчість Т. Шевченка ґрунтується на національних українських традиціях і знакова для України. The article determines that the first works in the history of Ukrainian literature “An Outline of the History of Ukrainian Literature” by M. Petrov (written in Russian) and “The History of Russian Literature” by O. Ohonovskyi (written in Ukrainian) are the central ones in the description of the social and political, cultural, language and literary situation in Ukraine during the years 1880–1890. M. Petrov shows “compromise” / “eclectic” attitude: while reading the works of T. Shevchenko he gives evidence of the Pan-Slavic world outlook orientation with the predominance of the sympathy for Russia and explains the idea of the intense influence of imperial literature upon Kobzar and the whole Ukrainian literature emphasizing on the necessity of the studying of the history of Ukrainian literature. But O. Ohonovskyi proves the independence and organicity of the Ukrainian culture. According to his conception the works of T. Shevchenko are based on the national Ukrainian traditions and they are symbolic for Ukraine. In the methodological aspect M. Petrov is still in the limits of the cultural and historical school but O. Ohonovskyi uses the ways of the formal, philological and aesthetic analysis besides the cultural and historical, bio- and bibliographical scientific approaches. Both scientists use the elements of the comparative research. “An Outline…” by M. Petrov is the illustration of the development of the literary thought in the materialistic and positivist period. The period of the antipositivist turning point on the way to the formation of the modern study of literature is connected with “The History…” by O. Ohonovskyi. O. Ohonovskyi performed deeper analysis of the works of T. Shevchenko.
The Works of T. Shevchenko in the Reception of M. Petrov and O. Ohonovskyi: the Problem of Formation of the Study of Shevchenko’s Inheritance
Keywords: Т. Шевченко; історія української літератури; рецепція; методологія; національне питання; культурно-історична школа; антипозитивістський злам; T. Shevchenko; history of Ukrainian literature; reception; methodology; national problem; cultural and historical school; antipositivist turning point